Bentonite-Yeast Binder Mitigates the Adverse Effects of Aflatoxin B1 on Intestinal Integrity and Performance in Broiler Chickens - Wahyudi, A. S.; Hidayaturrohman, N.; Agus, A.; Ariyadi, B.; Akbar, F. F.; Noor, I. H. M.; Anas, M. A. (Tropical Animal Science Journal, 2026)
Chronic exposure to aflatoxin may induce intestinal dysfunction and impair poultry productivity. The objective of this study was to evaluate the efficacy of toxin binders composed of bentonite, yeast cell wall, curcumin, and cinnamon in binding and mitigating the toxicity of aflatoxin B1 (AFB₁) in broiler chickens. The in vitro tests used four different toxin binder treatments: 100% bentonite (BEN), 100% yeast cell wall (YEAST), 50% bentonite + 50% yeast cell wall (BEN+Y), and 47.5% bentonite + 47.5% 3% curcumin, 2% cinnamon, and yeast cell wall (COMB). Two hundred eighty-eight male day-old chicks (DOC) were used in in vivo treatments and divided into six dietary treatments: basal control diet (CTRL), basal diet with 300 ppb AFB₁ (AF), basal diet plus BEN+Y (CTRL-A), basal diet + COMB (CTRL-B), AF + BEN+Y (AF-A), and AF + COMB (AF-B). Each treatment consisted of six replicates with eight birds per replicate. In vitro results indicated that BEN had the strongest AFB₁ binding capacity (p